Intergenerational occupational persistence: Recent evidence from Indian states - Sweta Lahiri; Tushar K. Nandi (Journal of Asian Development Research (JADR), 2020)
This article studies intergenerational occupational persistence using three recent rounds of a nationally representative sample survey from India. More than 60% of Indians are employed in the industry where their fathers are also employed. We find that individuals from Scheduled Tribes (ST) and Hindus have higher occupational persistence than those from the General Class (GEN) and Muslims, respectively. Persistence in general is higher in rural areas. We find considerable interstate and intrastate variations in the incidence across General Category States (GCSs) and Special Category States (SCSs). It has remained almost unchanged among GCSs on average, whereas it has decreased gradually for SCSs. Large inter-regional disparity exists within states between rural and urban areas and between capital and non-capital districts. Such disparity is found to be higher among GCSs. Bihar, Madhya Pradesh, Chhattisgarh and Jharkhand are the GCSs with large and increasing occupational persistence. Nagaland, Arunachal Pradesh, Meghalaya and Mizoram are the SCSs with persistence of above 70%. Using a probit estimation analysis, we find family background (father's education in rural area and ownership of productive assets) to have a significant and consistent influence on intergenerational persistence compared to own education. Results in general indicate that background factors play a stronger role than education does in the choice of occupation among Indians.
Keywords: 330; Intergenerational persistence; occupational mobility; labour market; transition; India